Vem vill äta surmört? - Arnstberg, Karl-Olof (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
When you as a traveller or field worker encounter foreign cultures, food could be most problematic. This short essay is based on the writers’ memories of food, from childhood and onwards. What is fit for food and what is not? Strange meals leave strong memories.